Online platforms, economic integration and Europe's rent-seeking society: Why online platforms deliver on what EU governments fail to achieve - Matthias Bauer (European Centre for International Political Economy (ECIPE), 2018)
Online platforms create "more perfect" markets. Online platforms are a market-driven cure to the imperfections of the EU's incomplete Single Market. Platforms provide well-functioning technical infrastructures that allow users to easily deal with country-specific legislation in the EU, e.g. VAT and invoicing requirements, consumer protection laws, sector-specific licenses and the particularities of national contract law. Modern online platforms have "skin in the game". They have an intrinsic motivation to create value for, and trust between, users and to enforce high and widely accepted standards for business conduct. In the EU, therefore, platforms encourage value-adding interactions that would not emerge without platforms when markets are locked by regulations and barriers that effectively protect insiders and deter new entrants. By doing so, platforms help consumers and businesses to "bypass" the effects of rent-seeking activities in the EU, which are at the root of significant differences in Member State regulations - and which for a long time have been known for being harmful to cross-border trade and economic integration and convergence in the EU. The EU and some Member State governments are neither unique nor extreme in their political calls to restrict or even ban certain platform businesses from operating. Yet, Europe's persistent hesitation - sometimes outright hostility - to platforms has to be seen in a broader perspective of political power and control. In the EU, old-fashioned national regulators have an organisational incentive to stick to and defend old approaches to regulation. In many cases, they have an intrinsic incentive to respond to vested interests in business and civil society. At the same time, through a bottom-up trial-and-error process, online platforms culturally appropriate customs and practices of governments and regulatory authorities in regulating markets and commercial behaviour, which are often "unacknowledged" by policymakers or considered "inappropriate". However, policymakers' hostilities towards modern online platforms disincentivise innovative companies to invest, grow and expand within and beyond the EU, with adverse implications for the Single European Market.
Keywords: 330